Mathematics student teachers' task design processes: The case of History, Theory, Technology, and Modeling - Çağlar Naci Hıdıroğlu (Journal of Pedagogical Research, 2022)
This study adopts a holistic single-case design to explain the task design processes of mathematics student teachers (MSTs) regarding History, Theory, Technology, and Modeling (HTTM). A criterion sampling method was used to select nine MSTs who had successfully completed algorithms and programming course. Video analyses, written answer sheets, scratch papers, and GeoGebra files were used to obtain data, including the views of MSTs on HTTM task design. Data analysis was performed using a content analysis method based on the theoretical framework of HTTM learning. The results revealed that HTTM design processes included task, focus/origin, problem, design (prototype), results, and approved reports. Furthermore, the mental steps that connected these basic components were found to be investigating, exploring, designing, evaluating, revising, and reporting. One of the key challenges experienced by the MSTs was found to be spending a great amount of time especially while determining a focus. The study has been finalised with a set of suggestions for future designs.